find the dervative of

  • Xsinx from 1st principle

y =xsinxLet δy be the increment in y , corresponding to increase in δx.y + δy = (x+δx) sin(x+δx)δy =(x+δx) sin(x+δx) - xsinxDividing throughout by δx, we getδyδx  = (x+δx) sin(x+δx) - xsinxδxOr dydx=limδx0δyδx= limδx0(x+δx) sin(x+δx) - xsinxδx= limδx0[x{sin(x+δx)-sinx}δx+sin(x+δx)]=limδx0[x{sin(x+δx)-sinx}δx] +limδx0sin((x+δx))=limδx0[x{sin(x+δx)-sinx}δx] +sinx=limδx0[2xcos(x+δx2)sinδx2δx] + sinx= {x×limδx0cos(x+δx2) ×limδx0sinδx2δx2}+sinx=xcosx+ sinx   (Ans)

  • 26
What are you looking for?